Ciri Limbah Pemanenan Kayu di Hutan Rawa Gambut Tropika - Ujang Suwarna; Juang Rata Matangaran; . Morizon (Institut Pertanian Bogor, 2013)
Effectiveness of timber harvesting in peat swamp forest is low. It is indicated by highly logging waste caused by timber harvesting operation. Thus, logging waste should be studied to describe characteristic and volume of logging waste in locations of compartment, landing, skidding track, and hauling road. The waste can be in the form of stumps, stems, and branches with diameter above 30 cm. Data of the waste was collected from 6 sample plots consisted of 3 plots in mechanized plots and 3 plots in traditional plots. Most of the waste found in location of compartment that caused by felling activities. Average volume of waste in traditional plots was 7.81 m3/ha that was found in location of compartment. The average volume of waste in the mechanized plots was 19.75 m3/ha, consisted of 16.90 m3/ha (85.57%) in location of compartment and 2.85 m3/ha (14.43%) in landing point. Logging waste can be minimized by providing appropriate training regularly and increase techniques of timber harvesting in the field.